2015
DOI: 10.1002/adma.201502574
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Modified Interface Controls Transition from VCM to ECM Switching Modes in Ta/TaOx Based Memristive Devices

Abstract: By modification of the electrode-solid-electrolyte interface with graphene, transit from valence change memories (VCM) to electrochemical metallization memories (ECM) in the cell Ta(C)/Ta2 O5 /Pt is demonstrated, thus, bridging both mechanisms. The ECM operation is discussed in the light of Ta-cation mobility in TaOx . The crucial role of electrochemical processes and moisture in the resistive switching process is also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
159
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 36 publications
8
159
0
1
Order By: Relevance
“…Thus, we confirm our recent observations, showing a typical ECM type of switching in TaO x -based devices, explained by Ta ion motion and redox reaction. 23,29 Moreover, formation of Ta filaments, 30 precipitation of Ta metal within TaO x upon cycling, 31,32 and first-principles calculations confirm metallic Ta is formed and is stable within the TaO x matrix, leading to metallic conducting filaments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we confirm our recent observations, showing a typical ECM type of switching in TaO x -based devices, explained by Ta ion motion and redox reaction. 23,29 Moreover, formation of Ta filaments, 30 precipitation of Ta metal within TaO x upon cycling, 31,32 and first-principles calculations confirm metallic Ta is formed and is stable within the TaO x matrix, leading to metallic conducting filaments.…”
Section: Resultsmentioning
confidence: 99%
“…Exposing the UHV-annealed TaO x film to the atmosphere leads to instant oxidation of the TaO x surface ( Figure S3) and also absorption of moisture, 29 and this, we believe, is the main reason for the change of the switching mechanism. The samples exposed to the atmosphere showed LRS after SET with anodic tip potential, i.e., reactions c and d at the surface and reactions a and b at the interface.…”
mentioning
confidence: 99%
“…[8] Effects of moisture were already reported for ECM cells based on oxides, e.g., Ta 2 O 5 [8][9][10] and SiO 2 . [11][12][13] It has also been shown that it affects the electrical characteristics in SrTiO 3−x [14] and Ta 2 O 5 [6] -based VCM devices as well. However, the detailed mechanism of this influence in relation to the resistive switching has not been discussed and the question on the influence of oxygen gas, also naturally present in the environment is still open.…”
Section: Introductionmentioning
confidence: 99%
“…However, new studies have demonstrated that the cations in such oxides are often mobile and can participate in the switching process as well. [5,6] Applying a voltage of opposite polarity, the formed filament is partially reoxidized within a thin region facing the high work function metal electrode, defining the OFF state. By modulation of the Schottky barrier at this interface reversible switching between the LRS and HRS is possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation